PENDIDIK DALAM PERSPEKTIF HADITS - Awaliyah, Mursyidatul; Mardiana, Mardiana; Muhaimin, Ahmad (STIT Darul Hijrah Martapura, 2024)
ABSTRACTTeachers in the Islamic view are people who play a role in the spiritual development and physical growth of students so that they can carry out their duties as servants or caliphs on earth according to Islamic teachings. An teacher should not be harsh and make things difficult for students because in accordance with the Hadith it is stated that the Prophet Muhammad SAW was sent as an teacher who made things easier, not difficult. The teacher is the representative of parents in the home environment, and their role in the school environment is to train students to achieve predetermined goals and make themselves human beings who do not deviate by providing examples that can be imitated, because the teacher is a learning resource, facilitator, person who manages learning, people who can provide instructions to students, or people who are called demonstrators, and are people who are able to realize ideas that exist in the world of education. The type of research used is Library Research. The main data source in this research is hadith manuscripts about teachers and the secondary sources in this research are books and journals that are relevant to the research.ABSTRAKPendidik dalam pandangan Islam merupakan orang yang berperan dalam perkembangan rohani dan pertumbuhan jasmani peserta didik agar bisa menjalankan tugas-tugas sebagai seorang hamba ataupun khalifah di bumi sesuai ajaran Islam. Seorang pendidik tidak boleh bersikap keras dan menyulitkan peserta didik karena sesuai dengan Hadits yang disebutkan bahwa Nabi Muhammad SAW diutus sebagai pendidik yang mempermudah bukan mempersulit. Guru merupakan wakil orang tua di lingkungan rumah, dan peranannya di lingkungan sekolah adalah melatih siswa mencapai tujuan yang telah ditentukan serta menjadikan dirinya sebagai manusia yang tidak menyimpang dengan memberikan contoh yang dapat ditiru, karena guru sebagai sumber belajar, fasilitator, orang yang mengelola pembelajaran, orang yang dapat memberikan petunjuk kepada peserta didik, atau orang yang disebut demonstrator, serta menjadi orang yang mampu mewujudkan ide-ide yang ada dalam dunia pendidikan. Jenis penelitian yang digunakan adalah Library Research (Kajian Pustaka). Sumber data utama pada penelitian ini adalah manuskrip hadits tentang pendidik serta yang menjadi sumber sekunder dalam penelitian ini adalah buku dan jurnal yang relevan dengan penelitian.